LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF CATLA CATLA (HAMILTON) AND LABEO ROHITA (HAMILTON) FROM DAYA RESERVOIR, UDAIPUR (RAJASTHAN) - Kumar, Raj; Sharma, B K; Sharma, L L; Upadhyay, B (Journal of the Inland Fisheries Society of India, 2016)
LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OFCATLA CATLA (HAMILTON) AND LABEO ROHITA (HAMILTON) FROMDAYA RESERVOIR, UDAIPUR (RAJASTHAN)